Hybrid Projection Algorithm for Two Finite Families of Asymptotically Quasi ϕ-Nonexpansive Mappings in Reflexive Banach Spaces. (2nd January 2018) - Hieu, Nguyen Trung; Dung, Nguyen Van
ABSTRACT: In this paper, we introduce a hybrid projection algorithm for two finite families of asymptotically quasi ϕ -nonexpansive mappings to establish a convergence theorem in smooth, strictly convex, and reflexive Banach spaces. As applications, we state the convergence of hybrid projection algorithm for two finite families of asymptotically quasi-nonexpansive mappings in Hilbert spaces and the convergence for a system of equilibrium problems.